Reading writing right : essays presented in honour of Prof. Elna Mouton - Punt, J. (Jeremy); Nel, Marius J. (Sun Press, 2018)
In a collection of essays, former students, colleagues and friends of Prof Elna Mouton honour her life, career and scholarly contributions upon her retirement from Stellenbosch University. The various essays interact with Prof Mouton's concern for biblical hermeneutics, ethics and the interactions and connections between the two, ultimately illustrating the width and variety of interest that her work stimulated and which it interacted with.